2015
DOI: 10.1097/prs.0000000000001710
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Distraction Osteogenesis in Low-Weight Neonates with Robin Sequence

Abstract: Background: The aim of this study is to evaluate the efficacy, safety profile and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…There were no increased risks of transfusion, tracheostomy, or mechanical ventilation. Only 1 previous study indirectly compared MDO outcomes by surgical age (Tahiri et al, 2015). Those authors found that low distraction weight (<4 kg) did not decrease clinical success or increase complications (Tahiri et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no increased risks of transfusion, tracheostomy, or mechanical ventilation. Only 1 previous study indirectly compared MDO outcomes by surgical age (Tahiri et al, 2015). Those authors found that low distraction weight (<4 kg) did not decrease clinical success or increase complications (Tahiri et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 previous study indirectly compared MDO outcomes by surgical age (Tahiri et al, 2015). Those authors found that low distraction weight (<4 kg) did not decrease clinical success or increase complications (Tahiri et al, 2015). In that study, the mean age of low-weight patients was 23 days, whereas the mean age of controls was 2.7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-nine percent (289/323) of subjects treated with TLA avoided tracheostomy. In a large MDO cohort study (34% syndromic), tracheostomy was avoided in 93% (76/81) of subjects after 22 months of follow up 106 . Tracheostomy was avoided in 89% of a large TLA cohort study (45% syndromic) 36 .…”
Section: Airway Outcomesmentioning
confidence: 99%
“…Previous studies have advocated for advancing the mandible to the limit of the distractor or until a class III occlusion, or anatomical overcorrection, has been achieved. 10,11,6,24 At our institution, we have found success with titrating distraction based on comprehensive 16-channel bedside PSG studies obtained immediately after initial distraction to stratify patients with persistent OSA. We feel that such a titration measure is also critical to avoid unnecessary and potentially disfiguring “overcorrections,” which is no small matter considering a majority of these patients have associated cleft palate and poor midfacial growth potential.…”
Section: Discussionmentioning
confidence: 99%